Doubly carbon-branched pentoses: synthesis of both enantiomers of 2.4-di-C-methyl arabinose and 2-deoxy-2,4-di-C-methyl arabinose using only acetonide protection - Booth, K; Jenkinson, S; Best, D; Fernandez Nieto, F; Estevez, R; Wormald, M; Weymouth-Wilson, A; Fleet, G (2009)
An acetonide is the only protecting group used in the synthesis of both the enantiomers of 2,4-di-C-methyl arabinose and 2-deoxy-2,4-di-C-methyl arabinose via the enantiomeric 3-C-methyl-l-erythronolactone [from 2-C-methyl-d-ribono-lactone or d-ribose] and 3-C-methyl-d-erythronolactone [from d-tagatose or l-ribose]. NMR studies on unprotected C-methyl arabinoses show that methyl branching significantly affects the ratios of pyranose and furanose forms present in aqueous solution. © 2009 Elsevier Ltd. All rights reserved.